2011
DOI: 10.21608/egyjs.2011.114932
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Some Indigenous Cyanoprokaryota Isolates Based on Morphological and Physiological Characterizations

Abstract: Forty-two cyanoprokaryota strains were isolated from 10 diverse sites along Sharkia Governorate, Egypt (7 sites representing the fertile soils and 3 sites representing the new reclaimed soils). Eight genera and 11 species of N 2 -fixing cyanoprokaryota were identified based on available morphological distinction and physiological characterization. On the basis of the obtained results, we classified these isolates to 3 genera and 5 species isolated from fertile soils and 7 genera and 8 species isolated from new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Anabaena oryzae SOS13 strain used in the present study was previously isolated from rice fields in Sharkia Governorate, Egypt and identified based on morphological and physiological characteristics (Salem et al, 2011 andAli 2012). This strain was fully identified using sequences of 16S ribosomal RNA gene and has been deposited in Gene Bank .…”
Section: Test Materialsmentioning
confidence: 99%
“…Anabaena oryzae SOS13 strain used in the present study was previously isolated from rice fields in Sharkia Governorate, Egypt and identified based on morphological and physiological characteristics (Salem et al, 2011 andAli 2012). This strain was fully identified using sequences of 16S ribosomal RNA gene and has been deposited in Gene Bank .…”
Section: Test Materialsmentioning
confidence: 99%